Linking patient experience to customer delight in the private laboratory service - Puspa Haryani Widyowati; Ferdi Antonio; Andy Andy (Administrative Sciences, 2023)
The goal of this study was to analyse the influence of the antecedents of patient experience, namely staff appearance, laboratory staff attitude, information clarity, staff responsiveness, laboratory ambience, phlebotomy process, laboratory technology, and report results, which furtherly generate customer delight and drive favourable intentions such as revisit intentions to the laboratory and willingness to share and post on social media. By extending earlier studies and using data from a leading private clinical laboratory service, this study suggests a new insight. A quantitative study with a survey is used with a cross-sectional data approach. The sample was taken purposively from customers who have had laboratory services at the laboratory, particularly from customers who have undergone the phlebotomy process. The 186 samples that complied with the criteria were examined using the PLS-SEM method. The findings demonstrated that the eight antecedents show a high probability of influencing the patient experience, with the phlebotomy process found as the predominant antecedent, followed by laboratory staff attitude and patient perception of laboratory technology. Further, this study found strong evidence that patient experience could generate customer delight, which drives the revisit intention and willingness to share and post positive things on social media. Openness is found to strengthen that process. The results of this study revealed that the higher the patient's experience through their journey, the higher the probability of delight could exist in the context of service provided in the private clinical laboratory. Thus, it is worth considering by the clinic management to develop a more effective business.
Keywords: 350; antecedents; behavioural intention; customer delight; laboratory; patient experience